2019
DOI: 10.1002/adma.201902479
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High‐Performance Silver Mesh for Transparent Glass Heaters via Electric‐Field‐Driven Microscale 3D Printing and UV‐Assisted Microtransfer

Abstract: nature, and harsh processing conditions of the ITO and the scarcity of the indium limit the further application for the THs. [3,4] As such, recent studies have proposed several emerging materials for the next-generation TCF to replace ITO, including carbon-based materials, [5][6][7][8] metal nanowires (NWs) or nanofibers (NFs), [9][10][11][12][13][14][15] metal meshes, [16][17][18] conductive polymers, [19] and hybrid materials. [1,[20][21][22] However, the cost, mechanical robustness, and trade-off between tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 53 publications
0
96
0
Order By: Relevance
“…Aiming at the shortcomings of the existing nano-silver paste and the problems that the existing technology cannot achieve, such as the stable and continuous printing of high viscosity or a high solid content nano-silver paste, we develop a nano-silver paste with a content of 75% by weight, good dispersing properties, and electrical properties. Meanwhile, electric-field-driven (EFD) micro-scale 3D printing technology is used to print the silver paste to verify the printing characteristics of silver paste [33,34]. In this paper, we discuss and analyze the fabrication details and properties of the silver paste and the printing characteristics of silver paste via EFD micro-scale 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the shortcomings of the existing nano-silver paste and the problems that the existing technology cannot achieve, such as the stable and continuous printing of high viscosity or a high solid content nano-silver paste, we develop a nano-silver paste with a content of 75% by weight, good dispersing properties, and electrical properties. Meanwhile, electric-field-driven (EFD) micro-scale 3D printing technology is used to print the silver paste to verify the printing characteristics of silver paste [33,34]. In this paper, we discuss and analyze the fabrication details and properties of the silver paste and the printing characteristics of silver paste via EFD micro-scale 3D printing technology.…”
Section: Introductionmentioning
confidence: 99%
“…where j is the current density (A/m 2 ), E p is the enhanced electric field (kV/m), and C and D are constant. From Equation (1), it can be found that the current density depends on electric field intensity, the higher the electric field intensity, the higher the current density. Considering the geometrical shape of the micro-peaks, the enhanced electric field at the micro-peaks on the electrode surface can be expressed as follows [19]: E p = U r t 0.75 l g 0.25 (2) where r t is the tip radius of micro-peaks (m), U is the voltage between electrodes, l g is the discharge gap (m).…”
Section: Formation and Expansion Of Discharge Plasmas Of Micro-edmmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to precision machining technology and methods [1,2]. As one of the most popular microfabrication methods, micro-electrical discharge machining (micro-EDM) has been widely applied to fabricate various difficult-to-cut materials [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing market demand for miniaturization and the precision of products, micro-processing technology has become one of the important indicators to measure a country's scientific and technological strength [1][2][3]. Micro-electrical discharge machining (micro-EDM) has become one of the most popular microfabrication technologies due to the advantage of machining electrically conductive materials without direct contact [4][5][6].…”
Section: Introductionmentioning
confidence: 99%